In Situ Recrystallization of Co-Evaporated Cu(In,Ga)Se2 Thin Films by Copper Chloride Vapor Treatment towards Solar Cell Applications - Deewakar Poudel (Energies, 2021)
Cu(In,Ga)Se2 (or CIGS) thin films and devices were fabricated using a modified three-stage process. Using high deposition rates and a low temperature during the process, a copper chloride vapor treatment was introduced in between the second and third stages to enhance the films properties. X-ray diffraction and scanning electron microscopy demonstrate that drastic changes occur after this recrystallization process, yielding films with much larger grains. Secondary ion mass spectrometry shows that the depth profile of many elements is not modified (such as Cu, In and Se) while others change dramatically (such as Ga and Na). Because of the competing effects of these changes, not all parameters of the solar cells are enhanced, yielding an increase of 15% in the device efficiency at the most.